Design, simulation and fabrication of piezoelectric micro generators for aero acoustic applications - Md Ralib @ Md Raghib, Aliza 'Aini; Nordin, Anis Nurashikin; Othman, Raihan; Salleh, Hanim (Springer Berlin / Heidelberg, 2011)
Energy harvesters based on acoustic vibration sources can generate electrical power through piezoelectric transduction. Significant miniaturization of electro mechanical devices using MEMS fabrication technology has encouraged the creation of portable, miniature energy harvesters. A niche application is aero acoustics, where wasted, high dB and high frequency sound generated by aircrafts are transformed into useful energy. Having selfpowered, miniature acoustic sensors allows noise detection monitoring systems to be self-sustaining. This paper illustrates an Aluminium doped Zinc Oxide (AZO) cantilever beam on stainless steel substrate with a top copper electrode. Design and finite element modelling of the design was conducted using CoventorwareTM. The AZO piezoelectric thin film was RF-sputtered on the stainless steel substrate. Characterizations were performed using X-ray diffraction (XRD) and scanning electron microscopy (SEM) to evaluate the piezoelectric qualities and surface morphology, respectively. Experimental measurements indicate approximately 345.4 mV AC output voltage (open circuit voltage) is produced at vibration frequencies of 30 kHz. This is in accordance with the CoventorwareTM simulation results. This measured power level is sufficient to power a miniature wireless acoustic sensor nodes to monitor noise generated by aircrafts.